The Improving Market Performance of MSMEs in Banyumas: Digital Marketing, Digital Accounting and Competitive Strategy: Meningkatkan Kinerja Pasar UMKM di Banyumas: Pemasaran Digital, Akuntansi Digital, dan Strategi Bersaing - Nur Isna Inayati; Sevian Anggi; Suryo Budi Santoso; Selamet Eko Budi Santoso (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to analyze the impact of digital marketing, digital accounting, and competitive strategies on enhancing the market performance of micro, small, and medium enterprises (MSMEs) in the digital era. Given the significant challenges and opportunities faced by MSMEs, this study explores how digital marketing can expand market reach and improve customer engagement, while digital accounting enhances financial transparency and operational efficiency. Additionally, competitive strategy is identified as a crucial factor in establishing a sustainable competitive advantage. The study focuses on MSMEs in Banyumas Regency, utilizing a sample of 106 respondents. Data analysis was conducted using Partial Least Squares (PLS) statistical methods. The findings indicate that digital marketing, digital accounting, and competitive strategy positively influence the market performance of MSMEs. This research underscores the importance of adopting digital technologies in MSME operations, demonstrating their effectiveness in facilitating various business activities and improving overall competitiveness.